Common statistical errors in systematic reviews: A tutorial - Kanellopoulou, Afroditi; Dwan, Kerry; Richardson, Rachel (Cochrane evidence synthesis and methods, 2025)
The aim of this article is to present the most common statistical errors in meta‐analyses included in systematic reviews; these are confusing standard deviation and standard error, using heterogeneity estimators for choosing between a common‐effect and random‐effects model, improper handling of multiarm trials, and unnecessary and misinterpreted subgroup analyses. We introduce some useful terminology and explain what authors can do to avoid these errors and how peer reviewers can spot them. We have also developed a micro‐learning module to provide practical hands‐on tutorial. The aim of this article is to present the most common statistical errors in meta‐analyses included in systematic reviews; these are confusing standard deviation and standard error, using heterogeneity estimators for choosing between a common‐effect and random‐effects model, improper handling of multiarm trials, and unnecessary and misinterpreted subgroup analyses. We introduce some useful terminology and explain what authors can do to avoid these errors and how peer reviewers can spot them. We have also developed a micro‐learning module to provide practical hands‐on tutorial. Common Statistical Errors micro learning module